Bulk flow properties of wheat - Bian, Qi (Kansas State University, 2014)
Consistent and reliable flow of bulk wheat from hoppers and silos is very significant in wheat handling and processing. Bulk wheat flow challenges such as inconsistent flow, arching, etc., are common during handling. The irregular size and non-uniformity of physical properties, the presence of impurities affects the flow behavior during discharge. Chaff and insects infested kernels are the two most common impurities present in wheat. In this research, the effect of these two impurities on their physical and flow properties of wheat were studied. Physical and flow indicators, such as bulk, tapped, particle densities, angle of repose, Hausner’s ratio, Carr index, and porosity measures the flowability of uncompacted bulk solids. Meanwhile, flow properties tested by shear testing principle based on Jenike’s method, simulated bulk wheat under pressure in bins/hoppers. The dynamic properties tested quantify the energy required to flow, compressibility and permeability at dynamic handling situations. Due to the presence of impurities and moisture content differences, bulk density and angle of repose of wheat varied from 801.54kg/m3 to 718.36kg/m3, and 23.6° to 38.4°, respectively. Angle of internal friction and wall friction angle that reflect interaction between particles and particle with bins/hopper walls, ranged from 23.95° to 43.13° and 15.46° to 20.33°, respectively. In addition to instrumental flow property evaluation, the flow profile, discharge rate, and particle velocity during hopper flow of bulk wheat was studied using Particle Image Velocimetry method. Mass flow and funnel flow hopper dimensions were used for this flow profile analysis. The discharge rate decreased from 1.67 to 1.12 kg/s for mass flow and 1.42 to 0.86 kg/s for funnel flow when the chaff in bulk wheat increased from 0% to 7.5% (weight basis). Analysis of the active flow zone indicated that bulk wheat without chaff had a uniform flow compared to wheat with chaff in the bulk. The findings from this study will be useful for design of hopper bottom bins and handling equipment based on the wheat quality and percent moisture content.
Keywords: Wheat; Bulk flow; Chaff; Insect damage kernel; Particle image velocimetry; Food Science (0359)